Entry into care following universal home-based HIV testing in rural KwaZulu-Natal, South Africa - (:unkn) unknown (My University, 2015)
Background: In a Universal Test and Treat (UTT) strategy, entry into care soon after HIV diagnosis is crucial to achieve optimal population-antiretroviral treatment (ART) coverage. We evaluated the rate of, and factors associated with, entry into care following home-based HIV testing in a cluster-randomised trial of the effect of immediate ART on HIV incidence in rural KwaZulu-Natal, South Africa.Methods: From March 2012 to May 2014, individuals ≥16 years in ten (2 x 5) clusters were offered home-based HIV testing; those ascertained HIV-positive were referred to TasP trial clinics and were offered universal and immediate ART (intervention clusters) or according to national guidelines (control clusters). Entry into care was defined as attending a TasP clinic within three months of referral among adults not actively in HIV care (no visit to local HIV programme within past 13 months). Associated factors were identified separately by sex, using multivariable logistic regression.Results: Overall, 1,205 adults (72.6% women) not actively in HIV care were referred to a TasP clinic. Of these, 405 (33.6%) attended a TasP clinic within three months (no difference between trial arms): 32.5% of women, 36.7% of men. Participants who ever visited the local HIV programme (n=360) were more likely to enter into care than those who didn’’t (women: adjusted Odd-Ratio (aOR) 1.76, 95% Confidence Interval [1.26-2.45]; men: 2.07 [1.18-3.64]). In women (n=875), those less likely to attend a TasP clinic within three months had completed some secondary school (0.51 [0.33-0.79]) or at least secondary school (0.47 [0.29-0.76]) versus below primary school; were living 1-2 km from a TasP clinic (0.43 [0.30-0.62]) or 2-5 km (0.40 [0.27-0.61]) versus < 1 km; didn’’t know anyone HIV+ within their family (0.60 [0.43-0.81]) and didn’’t agree that it is good to initiate ART as soon as possible if infected (0.47 [0.26-0.85]); among men (n=330), none of the factors exam
Keywords: African Research